Troutsmith : An Angler's Tales and Travels - Searock, Kevin (Book collections on Project MUSE., 2013)
In this collection of fishing essays, the author takes readers under the surface of this ancient sport, casting a spell of water-magic. Although trout are central to many of the stories, bluegills, bass, and other warm-water fish also grace these pages. The author writes about fly-tying, collecting fishing literature, journaling, and traveling in a way that makes the book a varied meditation on fishing and the outdoors.